Performance of a PCR assay for the rapid identification of the Klebsiella pneumoniae ST258 epidemic clone in Latin American clinical isolates - Gomez, Sonia A. (2016)
Fil: Gómez, Sonia Alejandra. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas. Departamento de Bacteriología. Servicio Antimicrobianos; Argentina.